Sistema de hipertermia hídrica controlada con mapeo para oncología ósea - Gutiérrez Martínez., Josefina; Rico Martínez., Genaro (Revista Mexicana de Ingenieria Biomedica, 2008)
The high thermal sensitivity of the cancerogenic cells has lead to use hyperthermia to sensitive and eradicate them with efficiency and effectiveness. The traditional procedure for malignant bone tumors is mainly amputation, affecting the life quality of children and adolescents. Hydro hyperthermia has been chosen to improve the prognoses in the extirpation and eradication of the malignant tumors in the Departamento de Tumores Óseos at Instituto Nacional de Rehabilitación. In this paper, it is showing the design, manufacture and operation of a system to generate, control and deliver heat energy into tumor: “Controlled Hydro Hyperthermia”. As well as, Bone Temperature Distribution. The system is a cheap, easy, affordable and secure system that represents a chance to preserve the extremity without to use any surgical appliance. The system has three parts: The first is the electromechanical device that provides temperature above 80 °C, last 30 min minimum. Second, the direct steam applicator. And finally the thermal mapping. At the moment, 19 patients, with bone tumor and pseudotumor in extremities, have been submitted to hydro hyperthermia procedure. 85.7% patients with osteosarcoma have had good prognostic and the hydro hyperthermia system has not any problem.